Comparative Sustainability Evaluation of Garlic Farming System: The Role of Integration and Partnerships in Karanganyar, Indonesia - Mei Tri Sundari; Endang Siti Rahayu; Heru Irianto; Sugiharti Mulya Handayani; Setyowati; Fanny Widadie (Jurnal Manajemen dan Agribisnis, 2026)
Background: Garlic is a strategic horticultural commodity in Indonesia with diverse benefits and high market demand. However, the sustainability of garlic farming faces several structural challenges, including low productivity, limited market access, weak institutional support, low technology adoption, and poor quality seeds.Purpose: This study aimed to evaluate the sustainability status of garlic farming, analyze performance differences, and identify sensitive attributes that influence sustainability.Design/methodology/approach: This study was conducted in Karanganyar Regency with 120 respondents in total. This study used a Rapid Appraisal (RAP) method with a Multidimensional Scaling (MDS) approach.Findings/Results: The results indicate that the multidimensional sustainability index of garlic farming is categorized as moderately sustainable (50–70). Farms adopting integrated farming with partnerships achieved the highest index (58.43), followed by non-integrated farms with partnerships (57.96), integrated farms without partnerships (54.61), and non-integrated farms without partnerships (54.17). The social dimension ranked the highest, followed by the ecological, economic, institutional, and technological dimensions. Leverage analysis identified 11 sensitive attributes, including farming experience, farmer group membership, water availability and conservation, marketing management, marketing institutions, seed availability, seed technology, bulb productivity, supporting policies, and organic fertilizer use. The simulation showed that improving these attributes could increase the multidimensional sustainability index by up to 26.76% in all categories.Conclusion: Enhancing sustainability should focus on technology adoption, strengthening marketing institutions, improving seed access, and developing adaptive policies. Originality/value (State of the art): This study shows that integrated interventions targeting these sensitive attributes are expected to facilitate the transition of garlic farming from “moderately sustainable” to “fully sustainable”. Keywords:  garlic, multidimensional scaling, RAP Analysis, influence sustainability, integrated farming